2021
DOI: 10.46367/iqtishaduna.v10i1.276
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Yang Mempengaruhi Minat Menggunakan Fintech Syariah

Abstract: This study aims to identify the factors that influence the interest of the people of Yogyakarta in using Islamic fintech by using the technology acceptance model (TAM). The sampling technique used purposive sampling so that the number of samples obtained was 150 respondents. This study was analyzed using a structural equation model partial least square (SEM-PLS) with the help of SmartPLS 3.2.9 software. The results of this study indicate that the intention to use sharia fintech is influenced by the individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
2
22

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 12 publications
(26 reference statements)
1
16
2
22
Order By: Relevance
“…This shows that there is a significant influence between Attitudes towards the satisfaction of Fintech Syariah Peer To Peer Lending in Indonesia. Thus hypothesis 1 is accepted, the results of this study are in line with research conducted by(Misissaifi & Sriyana, 2021), with the title Factors Affecting Interest in Using Islamic Fintech Hypothesis 2 H2: Perception affects the satisfaction of Fintech Syariah Peer To Peer Lending in Indonesia. Based on the test results contained in Table…”
supporting
confidence: 84%
“…This shows that there is a significant influence between Attitudes towards the satisfaction of Fintech Syariah Peer To Peer Lending in Indonesia. Thus hypothesis 1 is accepted, the results of this study are in line with research conducted by(Misissaifi & Sriyana, 2021), with the title Factors Affecting Interest in Using Islamic Fintech Hypothesis 2 H2: Perception affects the satisfaction of Fintech Syariah Peer To Peer Lending in Indonesia. Based on the test results contained in Table…”
supporting
confidence: 84%
“…Previous research was conducted by Misissaifi & Sriyana (2021) entitled "Factors Influencing Interest in Using Sharia Fintech using the Technology Acceptance Model (TAM)". In this study, the results showed that the factors that have the greatest role in accepting sharia fintech are attitudes and sharia compliance (Misissaifi & Sriyana, 2021). However, the research focuses on interest in using the application only.…”
Section: Introductionmentioning
confidence: 80%
“…The importance of sharia FinTech can also be seen from the point of view of equal distribution of income and economic justice, then it can also be used as an ethical alternative for society, especially for Muslims where FinTech sharia which is based on the principles of Islamic finance does not support the existence of various unethical practices including trade in weapons, liquor, pornography, gambling and others . So that Islamic FinTech can become a solution to the problems of the Islamic financial industry through the development of digital Islamic financial services (Misissaifi & Sriyana, 2021). The benefits of having sharia FinTech can be summarized, namely, helping MSME actors; free of usury, does not harm one party but benefits many parties; creating a process that is easier, more effective, efficient, economical, and safe (Wiyono, 2020).…”
Section: Sharia Fintechmentioning
confidence: 99%